Suture: Trauma and Trans Becoming - Cerankowski, KJ (Punctum Books, 2021)
"The landscape of trauma is scattered with ghosts. Wolves hunkering in the shadows. Memory's spectral persistence and evasion. Leaky bodies and selves gathered up in the storm of pain. Genders imposed and genders made. History's cruel excisions, scars, the spillage of wounds. A landscape in which we are nevertheless called to build home. Here, "storytelling is a kind of suturing."Combining memoir, lyrical essay, and cultural criticism, KJ Cerankowski's Suture: Trauma and Trans Becoming stitches together an embodied history of trauma and its ongoing impacts on the lived realities of trans, queer, and other marginalized subjects. Suture is a conjuration, a patchwork knitting of ghost stories attending to the wound as its own archive. It is a journey through many "transitions": of gender; through illness and chronic pain; from childhood to adulthood and back again; of psyche and form in the wake of abuse and through the work of healing; and of the self, becoming in and through the ongoingness of settler colonial violence and its attendant subjugations of diverse forms of life.Refusing a traditional binary-based gender transition narrative, as well as dominant psychoanalytic narratives of trauma that center an individual process of symptom, diagnosis, and cure, Suture explores the refractive nature of trauma's dispersed roots and lingering effects. If the wounds of trauma are disquiet apparitions--repetitions within the cut--these stories tend the seams through which the simultaneous loneliness of mourning and togetherness of queer intersubjective relations converge. Across these essays, healing, and indeed living, is a state of perpetual becoming, surviving, and loving, in the nonlinearities of trauma time, body-time, and queer time."